Repeated rational secret sharing, revisited. (2nd March 2012) - Wang, Yilei; Wang, Hao; Xu, Qiuliang
Rational Secret Sharing Scheme (RSSS) disposes the dilemma that several selfish players come together and willingly pool their shares to reconstruct a secret without a compulsory execution measure, while cooperation is not a strict optimisation. This paper introduces four punishment strategies and expands the perfect conclusions in infinitely repeated RSSS to show that cooperation will recur by means of some strategies. For finitely repeated RSSS, this paper verifies that there is no way for players to cooperate under perfect and complete information for backward induction. To overcome this difficulty, this paper relaxes conditions such as the types of players and the randomised strategies. It is proved that, given the different types and incomplete information, players will insist on cooperation in finitely repeated RSSS. In addition, we discuss repeated games in an extensive form and propose a 2-out-of-2 RSSS.